Enhancing patient safety outcomes through SBAR communication: A systematic review - Nanang Kosim; Saimi Saimi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: SBAR (Situation, Background, Assessment, Recommendation) is a structured communication framework designed to facilitate the logical and efficient transfer of information among healthcare professionals. This method supports the identification, assessment, and management of patient risks. Ineffective communication is a leading contributor to patient safety incidents; therefore, implementing structured communication like SBAR is essential for enhancing the quality and safety of healthcare delivery. Purpose: To explore and analyze the impact of SBAR communication on improving the effectiveness of patient safety within healthcare settings. Method: A systematic review approach in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A thorough search was conducted across multiple scholarly databases—Scopus, PubMed, ScienceDirect, and Google Scholar—using the keywords: